YOUTH LANGUAGE UNCOVERED: META-SYNTHETIC INSIGHTS INTO GEN Z AND GEN ALPHA SLANG - Paoleti, Veronika Deyanova; Mujahidah, Nur Fathiyya Zahira (University of Kuningan, 2025)
This study aims to analyze the linguistic behaviors of Gen Z and Gen Alpha, focusing on their use of slang, the influence of digital platforms, and the broader cultural and societal implications of their language practices. A meta-synthetic research design was employed, synthesizing data from 30 academic articles, conference proceedings, and credible publications spanning 2016–2024. Thematic synthesis techniques were applied, including coding, categorization into thematic areas, and meta-synthesis to identify patterns and trends. Quantitative metrics, such as the frequency of slang usage on platforms like TikTok and Instagram, were also analyzed to examine inter-generational differences. The findings reveal that both generations use slang as a cultural marker, with Gen Z favoring socio-political expressions such as